Regulation of immune response by Plasmodium-infected red blood cells. - Ndungu, F; Urban, B; Marsh, K; Langhorne, J (2005)
During the asexual blood stage infection of the human malaria parasite, Plasmodium falciparum, parasite-derived proteins are inserted onto the surface of the host red blood cell membrane. These proteins are highly variable and were originally thought only to mediate antigenic variation, and sequestration of parasites from peripheral circulation, thus enabling immune evasion. Recent studies have revealed that PfEMP-1 and other molecules on the P. falciparum-infected red blood cell (PfRBC) activate and modulate the immune response. In this review, we discuss how PfRBCs interact with antigen-presenting cells (APCs) and other cells of the immune system, and how such interactions could modulate the host response to Plasmodium infections.